The Insider's Guide to Writing The Perfect Resume - Weber, Karl, Kaplan, Rob (Peterson's, 2020)
Two veterans of the job-search maze bring you the steps and strategies you need to develop and write a winning resume-from eye-catching design tips to advice on word choice